2005
DOI: 10.1590/s1415-47572005000100028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of H2O2, Fe2+ and Fe3+ on curcumin-induced chromosomal aberrations in CHO cells

Abstract: The effects of H 2 O 2 , Fe 2+ and Fe 3+ on curcumin-induced clastogenicity were evaluated in CHO cells. Curcumin combined with H 2 O 2 did not increase the chromosomal aberrations more than expected based on a simple additive effect. In contrast, the combination of curcumin-Fe significantly decreased the total number of chromosomal aberrations and the number of abnormal metaphases. The clastogenicity of curcumin may be related to its pro-oxidant properties and its ability to generate free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Downregulation of various inflammatory cytokines such as TNF, interleukin (IL)-1, IL-6, IL-8, interferon, and some other chemokines are also carried by the circumin. [ 13 ] Considering the anti-inflammatory effect of turmeric and chlorhexidine mouthwash, the results of the present study were consistent with the results of Waghmare et al .,[ 14 ] Van der Weijden et al .,[ 15 ] Grundemann et al .,[ 16 ] and Leyes, et al . [ 17 ] The progression of disease progression was markedly reduced by the activity of curcumin as pro-oxidant and antioxidant by scavenging the free radical, a reducing agent and a DNA damage inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of various inflammatory cytokines such as TNF, interleukin (IL)-1, IL-6, IL-8, interferon, and some other chemokines are also carried by the circumin. [ 13 ] Considering the anti-inflammatory effect of turmeric and chlorhexidine mouthwash, the results of the present study were consistent with the results of Waghmare et al .,[ 14 ] Van der Weijden et al .,[ 15 ] Grundemann et al .,[ 16 ] and Leyes, et al . [ 17 ] The progression of disease progression was markedly reduced by the activity of curcumin as pro-oxidant and antioxidant by scavenging the free radical, a reducing agent and a DNA damage inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that curcumin is able to bind Fe, Mn and Cu as described above, there are relatively few studies of how such binding modulates the redox properties of curcumin. Studies involving the interaction of curcumin with Fe or Cu have indicated pro-oxidant effects, suggesting that the metal complexes are able to redox cycle, in analogy to the Fenton process [176,183,184]. Radicalscavenging effects are also noted for the Mn [172] and Cu [177] complexes of curcumin, either of hydroxyl radical or of superoxide.…”
Section: Redox Chemistrymentioning
confidence: 99%
“…The biological classification of curcumin as both pro-oxidant and antioxidant, is well supported by studies showing curcumin as a free radical scavenger, a reducing agent, and a DNA damage inhibitor, especially in the presence of Cu or Fe ions. Curcumin is able to bind to Fe, Mn and Cu that was reported to modulate the antioxidant properties [54][55][56] and radical scavenging effects [57,58] of this agent. In vitro studies have shown that curcumin inhibits nitric oxide and reactive oxygen species (ROS) production in macrophages [59,60]; it also inhibits lipo-oxygenase as well as cyclooxigenase in fibroblast cells of rats [61].…”
Section: Antioxidative Activity Of Curcuminmentioning
confidence: 99%